Design of core–shell titania–heteropolyacid–metal nanocomposites for photocatalytic reduction of CO2 to CO at ambient temperature. Issue 11 (19th September 2019) - Yu, Xiang; Moldovan, Simona; Ordomsky, Vitaly V.; Khodakov, Andrei Y.
Abstract : We report new efficient core–shell nanocomposites for photocatalytic CO2 to CO conversion at ambient temperature with enhanced yield and selectivity. Abstract : The photocatalytic conversion of CO2 not only reduces the greenhouse effect, but also provides value-added solar fuels and chemicals. Herein, we report the design of new efficient core–shell nanocomposites for selective photocatalytic CO2 to CO conversion, which occurs at ambient temperature. A combination of characterization techniques (TEM, STEM-EDX, XPS, XRD, FTIR photoluminescence) indicates that the CO2 reduction occurs over zinc species highly dispersed on the heteropolyacid/titania core–shell nanocomposites. These core–shell structures create a semiconductor heterojunction, which increases charge separation and the lifetime of charge carriers' and leads to higher electron flux. In situ FTIR investigation of the reaction mechanism revealed that the reaction involved surface zinc bicarbonates as key reaction intermediates. In a series of catalysts containing noble and transition metals, zinc phosphotungstic acid–titania nanocomposites exhibit high activity reaching 50 μmol CO g −1 h −1 and selectivity (73%) in the CO2 photocatalytic reduction to CO at ambient temperature. The competitive water splitting reaction has been significantly suppressed over the Zn sites in the presence of CO2 .